The sigma E subunit of Bacillus subtilis RNA polymerase is present in both forespore and mother cell compartments. - Carlson, H C (1989)
Bacillus subtilis cells harvested 3.5 h after the onset of sporulation (t3.5) were fractionated into extracts enriched in either mother cell or forespore components and were analyzed immunologically for sigma E and its precursor protein, P31. We determined by Western blot (immunoblot) analysis that equivalent amounts of P31 and sigma E were present in both mother cell and forespore extracts. This result implies that, although sigma E is not synthesized until a stage in development when the cell is partitioned into progenitor forespore and mother cell compartments, it probably directs the transcription of genes that are expressed in both of these structures.